Medication therapy management clinic: perception of healthcare professionals in a University medical center setting - Shah M; Markel Vaysman A; Wilken L (Pharmacy Practice, 2013)
Objective: To determine the overall perception and utilization of the pharmacist managed medication therapy management (MTM) clinic services, by healthcare professionals in a large, urban, university medical care setting.Methods: This was a cross-sectional, anonymous survey sent to 195 healthcare professionals, including physicians, nurses, and pharmacists at The University of Illinois Outpatient Care Center to determine their perception and utilization of the MTM clinic. The survey consisted of 12 questions and was delivered through a secure online application. Results: Sixty-two healthcare professionals (32%) completed the survey. 82% were familiar with the MTM clinic, and 63% had referred patients to the clinic. Medication adherence and disease state management was the most common reason for referral. Lack of knowledge on the appropriate referral procedure was the prominent reason for not referring patients to the MTM clinic. Of the providers that were aware of MTM services, 44% rated care as ‘excellent’, 44% as ‘good’, 5% as ‘fair’, and 0% stated ‘poor’. Strengths of MTM clinic identified by healthcare providers included in-depth education to patients, close follow-up, and detailed medication reconciliation provided by MTM clinic pharmacists. Of those familiar with MTM clinic, recommendations included; increase marketing efforts to raise awareness of the MTM clinic service, create collaborative practice agreements between MTM pharmacists and physicians, and ensure that progress notes are more concise.Conclusion: In a large, urban, academic institution MTM clinic is perceived as a valuable resource to optimize patient care by providing patients with in-depth education as it relates to their prescribed medications and disease states. These identified benefits of MTM clinic lead to frequent patient referrals specifically for aid with medication adherence and disease state management.